Magnesium Ions Inhibit the Expression of Tumor Necrosis Factor α and the Activity of γ-Secretase in a β-Amyloid Protein-Dependent Mechanism in APP/PS1 Transgenic Mice - Yu, Xin; Guan, Pei-Pei; Zhu, Di; Liang, Yun-Yue; Wang, Tao; Wang, Zhan-You; Wang, Pu (Frontiers in Molecular Neuroscience, 2018)
Alzheimer’s disease (AD) is a neurodegenerative disease characterized by cognitive impairment. The neuropathological features of AD are the aggregation of extracellular amyloid β-protein (Aβ) and tau phosphorylation. Recently, AD was found to be associated with magnesium ion (Mg2+) deficit and tumor necrosis factor-alpha (TNF-α) elevation in the serum or brains of AD patients. To study the relationship between Mg2+ and TNF-α, we used human- or mouse-derived glial and neuronal cell lines or APP/PS1 transgenic (Tg) mice as in vitro and in vivo experimental models, respectively. Our data demonstrates that magnesium-L-threonate (MgT) can decrease the expression of TNF-α by restoring the levels of Mg2+ in glial cells. In addition, PI3-K/AKT and NF-κB signals play critical roles in mediating the effects of Mg2+ on suppressing the expression of TNF-α. In neurons, Mg2+ elevation showed similar suppressive effects on the expression of presenilin enhancer 2 (PEN2) and nicastrin (NCT) through a PI3-K/AKT and NF-κB-dependent mechanism. As the major components of γ-secretase, overexpression of presenilin 1 (PS1), PEN2 and NCT potentially promote the synthesis of Aβ, which in turn activates TNF-α in glial cells. Reciprocally, TNF-α stimulates the expression of PEN2 and NCT in neurons. The crosstalk between TNF-α and Aβ in glial cells and neurons could ultimately aggravate the development and progression of AD.